L2 Reading Assessment from a Sociocultural Theory Perspective: The Contributions of Dynamic Assessment - Ali Kushki; Hossein Nassaji (MDPI AG, 2024)
Our understanding of assessing L2 reading has significantly expanded in recent years, including both theoretical and practical aspects. There is a growing consensus that reading comprehension involves multiple skills and subskills. Classroom-based assessment practices reflecting such conceptualizations have also become widely utilized. This article explores the Vygotskyan sociocultural theory (SCT) and its implications for L2 reading assessment, with a specific focus on dynamic assessment as an effective classroom-based approach for L2 reading and literacy instruction. We will review the research that has applied DA principles to the assessment and teaching of L2 reading. We conclude by outlining potential avenues for future DA research and L2 reading instruction.